A structural equation modelling evaluation of antecedents and interconnections of call centre agents' intention to quit - Chux Gervase Iwu; Abdullah Promise Opute; Aliyu Olayemi Abdullateef; Chuks Eresia-Eke; Tichaona Buzy Musikavanhu; Afeez Olalekan Jaiyeola (Journal of Risk and Financial Management, 2021)
Call centers play a significant role in the operational dynamics of different types of businesses. This is especially the case because a call center agent's demeanor can impair or engender customer satisfaction, which has ramifications for business patronage. Unfortunately, the pressures associated with the role of the call center agent have made staff attrition a norm in the industry. While this does not augur well for the call center or the organizations that they serve, the role of possible antecedents in the equation of staff attrition in South African call centers remains largely unexplored. Using a structural equation modeling approach, this study examined the interconnections between customer orientation, knowledge management, job satisfaction, and employees' intention to quit. Additionally, the mediating influence of job satisfaction on the association between customer orientation and knowledge management of the intention to quit is examined. This study found significant relationships between knowledge management, customer orientation, and job satisfaction and the dependent variable (intention to quit). In addition, this study establishes that the extent to which job satisfaction may mediate the influence on the intention to quit hinges on the organizational element considered. Two factors limit the extent to which the findings from this study can be generalized. First, this study focused on the call center setting in South Africa. Second, convenience sampling was used in this study. This study points to critical operational practices that call center managers can embrace toward enhancing job satisfaction and reducing intention to quit propensity. Using structural equation analysis, we contend that call centers in the South African setting would effectively address staff attrition if appropriate organizational practices are endorsed toward ensuring employee job satisfaction.
Keywords: 330; risk management; call center; customer orientation; employee turnover; intention to quit; job satisfaction; knowledge management